2019
DOI: 10.24203/ajeel.v7i1.5701
|View full text |Cite
|
Sign up to set email alerts
|

Factors causing Mathematics Anxiety of Senior High School Students in Calculus

Abstract: Mathematics anxiety impacts to the learner tremendously especially his scholastic performance, mastery of learning competencies and skills, and even the career choice. This study investigated the different factors causing mathematics anxiety in Calculus of senior high school students. The research design employed was mixed method. Qualitative techniques were used in determining the factors that caused the anxiety of the participants and descriptive design in determining the anxiety level of the students. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…Several past studies have discussed students' mathematics anxieties (Estonanto & Dio, 2019;Musa & Maat, 2021;Luttenberger et al, 2018). Musa and Maat (2021) reported that mathematical anxiety impacts students' emotions, thoughts, and actions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Several past studies have discussed students' mathematics anxieties (Estonanto & Dio, 2019;Musa & Maat, 2021;Luttenberger et al, 2018). Musa and Maat (2021) reported that mathematical anxiety impacts students' emotions, thoughts, and actions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another study, Estonanto and Dio (2019) investigated various factors causing mathematics anxiety related to the calculus of senior high school students. The study found eight factors of mathematical anxiety, namely lack of selfconfidence, interest and study habits, the role of the teacher, fear of failure, pressure from parents and peers, pressured quizzes and tests, poor skills in analysis, and the abstract nature of mathematical concepts (Estonanto & Dio, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Awofala and Odogwu (2017) revealed that mathematics anxiety level was significant in calculus cognitive failures and performance among the students. The high anxiety is also attributed to several major factors, including the abstract concepts of calculus, the teaching style, and the poor analytical skills of the students (Estonanto & Dio, 2019). This mathematics anxiety is so crucial that it will affect calculus mathematics performance (Estonanto, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the study of [4] as cited by the authors, the performance of the junior high school in mathematics was weak. Additionally, the study of [5] pointed out that the majority of the students were in the beginning level of mathematics proficiency. The strategies/approaches used by the majority of the teachers in teaching Basic Calculus are sometimes laborious and complicated for the students.…”
Section: Introductionmentioning
confidence: 99%